2014
DOI: 10.1021/ie404055z
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Control for Heat Exchangers in Recirculating Cooling Systems Using Treated Municipal Wastewater

Abstract: Treated municipal wastewater (MWW) is recognized as a viable alternative cooling water source for power generation. One of the key challenges for the successful use of the effluent from wastewater treatment facilities for cooling is the potential for significant condenser fouling when this water is concentrated as much as 4–6 times in recirculating cooling systems. In this study, two types of treated municipal wastewaters, namely secondary-treated MWW with pH adjustment (MWW_pH) and secondary-treated MWW subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…A fouling curve showing the development of the fouling resistance with time reflects surface deposition on the heat transfer surface (Figure 8.5) and reveals the impact of PMA on the control of crystalline fouling by calcium phosphate in the synthetic secondary treated MWW at four cycles of concentration (CoC 4) when pH is controlled at 7.8 [30]. A sampling rack section incorporating stainless steel specimen discs (5.61 cm 2 ) is included in the experimental systems to track the bulk precipitate deposition process.…”
Section: Water Recirculating System With Heated Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…A fouling curve showing the development of the fouling resistance with time reflects surface deposition on the heat transfer surface (Figure 8.5) and reveals the impact of PMA on the control of crystalline fouling by calcium phosphate in the synthetic secondary treated MWW at four cycles of concentration (CoC 4) when pH is controlled at 7.8 [30]. A sampling rack section incorporating stainless steel specimen discs (5.61 cm 2 ) is included in the experimental systems to track the bulk precipitate deposition process.…”
Section: Water Recirculating System With Heated Surfacementioning
confidence: 99%
“…Liu [30] has shown that typical antiscalants (e.g., PMA and HEDP) could extend the induction time for the transformation of amorphous calcium phosphate (ACP) to hydroxyapatite (HAP). Measured zeta potential exceeding AE20 mV is indicative of good particle stability, whereas the values below AE10 mV are deemed unstable.…”
Section: Inhibition Of Scale Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has summarized the equations used to calculate vertical forces that act on barium sulfate particles (Liu, 2013).…”
Section: Theoretical Calculation Of the Forces Acting On Barite Partimentioning
confidence: 99%
“…Open circulating cooling water system is widely used in process industry to cool off equipment and product, and to transfer waste heat into the environment [1,2]. Due to the evaporation and leakage of water, as well as the sewage of the system, this process brings about the consumption of water resources and the sewage drainage.…”
Section: Introductionmentioning
confidence: 99%